« Hennin, archives et micro ». Les archives des sœurs hospitalières de Beaune, de la collecte à la valorisation - Sonia Dollinger (In Situ)
For a public archive service, the collection of a private archival collection is always a delicate question. It is based on an exchange with the donor of the collection who, in handing over the archives to an institution, manifests his or her confidence in that institution for the proper management of the documents. What then is the relationship between the two parties? The example here of the archives of the Beaune ‘soeurs hospitalières’, the nursing sisters, is characteristic of the importance of the relationship between the donor and the receiving institution and raises questions about the archivist’s profession. What is the point in recovering a private archive collection? Beyond the normal tasks of saving part of the history of a commune by ordering and taking material care of the documents, it is also necessary to interpret them and make them available to as many people as possible, to diffuse information about a collection of papers of historical significance that goes beyond the scale of the small town of Beaune. Several possibilities are available to the archivist: communicating the documents to researchers in the archive reading room, organising film projections, putting the papers on line... The archivist can also play a part in making the collection even richer, for example by recording the oral memories of the nursing sisters still present at Beaune. In this way, the archivist is not only a transmitter of information, he or she is also a promoter of the information, making it visible to the general public.